Detection of specific IgM and IgG antibodies in acute canine monocytic ehrlichiosis that recognize recombinant gp36 antigens - Kaewmongkol, Sarawan (Heliyon, 2020)
The efficacy of antibody detection tools for all stages of Ehrlichia canis infections and for various genotypes remains unclear. We produced recombinant gp36 (rgp36) antigens from different isolates of Thai E. canis to confirm the immunoreactivities to these recombinant proteins from naturally infected dogs. Sera and blood samples were taken from 21 dogs naturally infected with E. canis and in the clinical stages of acute phase ehrlichiosis. The expression vectors and competent E. coli produced two isolates of rgp36. These two major rgp36s were recognized by the dogs' sera in Western blotting, with both anti-dog IgM and IgG used as secondary antibodies. The two different genotypes of these local recombinant immunoreactive proteins were gp36 subgroup A (isolate 1055) and subgroup B (isolate 533). The Western blot analyses successfully identified both specific IgM and IgG from the dogs' sera. Of all 21 cases, five dogs presented specific IgM, twenty dogs presented specific IgG, and the commercial test used found fifteen seropositive dogs. There were four dogs that presented both specific IgM and IgG. Only one dog presented specific IgM only. This report is the first identification of a specific IgM in dogs in response to acute infections with E. canis. The recombinant gp36 isolates may be useful as potential antigenic material for subsequent serological tests that have a high possibility for differentiating between acute, chronic, primary, and nonprimary infections with E. canis.